Visual Stimuli to Foster Philosophical Discussion in the University Classroom - Даниліна, Світлана Юріївна; Судорженко, Галина Петрівна (Київський національний університет імені Тараса Шевченка, 2026)
Fostering meaningful speaking activities in foreign language (FL) university classes presents a lot of challenges for the learners due to the complex nature of subjects discussed in university courses. This article explores the integration of visual art–specifically Albert Gleizes’ Composition with Guitar–as a pedagogical tool to stimulate discussion of Henri Bergson’s philosophical concepts, particularly his ideas of time and intuition, as well as their impact on the rise of modernist outlook. Drawing on existing research on the use of visual aids in ESP and FL instruction, the study highlights how visual stimuli enhance language acquisition, encourage critical thinking, and support the interpretation of abstract ideas. The classes that the article features were conducted with upper-intermediate philosophy students of English at KNU, who successfully engaged with Bergson’s theory of duration and the dynamic nature of perception through analysis of Cubist artwork; and with the students of Spanish at KNLU, who discussed how Bergsonian concepts ushered in the advent of modernism. The activity fostered the use of field-specific vocabulary and facilitated deeper philosophical reflection. Findings suggest that visual art not only improves fluency and communicative competence but also supports higher-order thinking by bridging language learning and disciplinary content. The article concludes that visual art represents a valuable, yet underutilized, resource in teaching philosophy and philology students, with strong potential to enhance both conceptual and linguistic understanding. Further research would be recommended to explore this interdisciplinary approach more systematically.

У статті розглядається використання творів мистецтва як ефективного інструменту для стимулювання мовлення на філософську тематику на заняттях з англійської для спеціальних цілей і практичних занять з іноземної мови. Зокрема, аналіз картини Альбера Глезіса “Композиція з гітарою” допоміг студентам осмислити і обговорити філософські ідеї Анрі Бергсона, які стосуються часу та інтуїції, а також їхнього впливу на виникнення модерністської течії у мистецтві. Візуальні стимули сприяли розвитку критичного мислення, активному засвоєнню фахової лексики та формуванню навичок висловлювання абстрактних ідей іноземною мовою. Дослідження підтверджує, що завдяки ілюструванню філософського змісту за допомогою творів мистецтва створюється продуктивне середовище для мовної практики та розуміння складних філософських концепцій. Такий підхід є перспективним напрямом для подальших досліджень у галузі викладання ESP для студентів неспеціальних факультетів і для викладання практики мови для студентів-філологів.
Позачасове мистецтво як засіб заохочення студентів до філософської дискусії про час
Keywords: викладання іноземних мов; заняття в університеті; іноземна мова для спеціальних цілей; філософія; практика мовлення; foreign language instruction; university classroom; ESP; philosophy; speaking practice